White South Africans in Colorado: understandings of apartheid and post-apartheid society - Weeber, Christine A., author (Colorado State University. Libraries, 2005)
This pilot study focuses on the experiences of two white ethnic groups within the South African immigrant population, Afrikaners and English-speakers, who came of age during two different phases of apartheid, between 1958-1978 and 1979-1993. Race, ethnicity, generational standing, class, and nationalism remain important fault lines, so my analysis is structured to differentiate between the entrenchment and reproduction of these identities during apartheid and the disruption of these in the post-apartheid era and in people's migration to the U.S. Using a phenomenological approach, I investigate three issues: experiences of being white, the culture of apartheid, and immigration. Among the themes that emerged from my interviews are the "schizophrenic" nature of life under apartheid; guilt and responsibility; questions of truth, propaganda, and brainwashing; "Afropessimism" and racism; what it meant to be white under apartheid versus the present 'box of being white'; the 'push factors' of affirmative action and crime; and perspectives of race and racism in the U.S. versus South Africa. I also examine whiteness in these two white ethnic groups and as perceived by black and Colored (mixed race) informants. My research addresses the question of whether or not essential characteristics of whiteness exist, cross-culturally, based on a history of whiteness-as-domination. By applying Pierre Bourdieu's practice theory to whiteness studies, I attempt to account for the complexities of whiteness in this population. Patterns within this population show how historical ideologies of whiteness as-domination shaped the habitus of whites during apartheid. Yet, important exceptions to these patterns point to how people's habitus can change, moving whites out of the 'box of being white,' which remains a significant push factor for emigration out of post-apartheid South Africa.
Keywords: Colorado; South Africans -- Colorado; Apartheid; Post-apartheid era; South Africa -- Emigration and immigration